Visual Integration of Genome-Wide Association Studies and Differential Expression Results with the Hidecan R Package. - Angelin-Bonnet O; Vignes M; Biggs PJ; Baldwin S; Thomson S (MDPI (Basel, Switzerland), 2024)
Background/Objectives: We present hidecan, an R package for generating visualisations that summarise the results of one or more genome-wide association studies (GWAS) and differential expression analyses, as well as manually curated candidate genes, e.g., extracted from the literature. This tool is applicable to all ploidy levels; we notably provide functionalities to facilitate the visualisation of GWAS results obtained for autotetraploid organisms with the GWASpoly package. Results: We illustrate the capabilities of hidecan with examples from two autotetraploid potato datasets. Conclusions: The hidecan package is implemented in R and is publicly available on the CRAN repository and on GitHub. A description of the package, as well as a detailed tutorial, is made available alongside the package. It is also part of the VIEWpoly tool for the visualisation and exploration of results from polyploids computational tools.
Keywords: R package; autotetraploid; differential expression; genome-wide association studies; visualisation; Genome-Wide Association Study; Solanum tuberosum; Software; Humans; Computational Biology